Analysis of Students' Needs in Developing Reading Skills: An Exploratory Study in Elementary Schools - Sutrisno, Detria Nur Aini; Slamet, STY; Yulisetiani, Septi; Sari, Diah Hayu Novita (Proceeding International Conference on Religion, Science and Education, 2025)
This study aims to analyze the needs of students in developing reading skills. Data sources consist of questionnaires by validating data through interviews. The subjects of the study consisted of 111 students and 5 elementary school class teachers. The findings in this study are the needs of elementary school students in developing reading skills. These needs consist of learning methods, learning models, learning media, and learning processes. The results of the analysis show that the percentage of each aspect of needs, namely learning methods, is 15%, learning models 20%, learning media 50%, and 15% for the learning process. Students want to improve their reading skills by following the process explained by the teacher through innovative learning media. The conclusion of this study is that it is necessary to design learning methods, models, and media that facilitate students to learn Indonesian reading comprehension material in a better way. "Web"-based learning media is one of the main factors and the highest percentage of results, namely 70%, which is needed to support reading comprehension skills.